Long-term Outcomes with Anti-TNF Therapy and Accelerated Step-up in the Prospective Pediatric Belgian Crohn's Disease Registry (BELCRO). Issue 9 (10th July 2017) - Wauters, Lucas; Smets, Françoise; De Greef, Elisabeth; Bontems, Patrick; Hoffman, Ilse; Hauser, Bruno; Alliet, Philippe; Arts, Wim; Peeters, Harald; Van Biervliet, Stephanie; Paquot, Isabelle; Van de Vijver, Els; et al.
Abstract : Background: Accelerated step-up or anti–tumor necrosis factor (TNF) before first remission is currently not recommended in pediatric Crohn's disease. Methods: Five-year follow-up data from a prospective observational cohort of children diagnosed with Crohn's disease in Belgium were analyzed. Disease severity was scored as inactive, mild, or moderate to severe. Remission or inactive disease was defined as sustained if lasting ≥2 years. Univariate analyses were performed between anti-TNF–exposed versus naive patients and anti-TNF before versus after first remission and correlations assessed with primary outcomes average disease severity and sustained remission. Results: A total of 91 patients (median [IQR] age 12.7 [10.9–14.8] yrs, 53% male) were included. Disease location was 12% L1, 23% L2, and 64% L3 with 76% upper gastrointestinal and 30% perianal involvement. Disease severity was 25% mild and 75% moderate to severe. Of 66 (73%) anti-TNF–exposed patients, 34 (52%) had accelerated step-up. Anti-TNF use was associated with age (13.1 [11.5–15.2] versus 11.8 [8.7–13.8] yrs; P < 0.05), L2 (29% versus 8%; P = 0.04), and average disease severity (1.7 [1.4–1.9] versus 1.4 [1.3–1.6]; P < 0.001). Duration of anti-TNF correlated with average disease severity (r = 0.32, P = 0.002). Accelerated step-up was also associated with age (13.3 [12.1–15.9] versus 12.5 [10.2–14.1]; P = 0.02) and average disease severity (1.8 [1.6–1.9] versus 1.6 [1.3–1.8]; P = 0.002). Duration of sustained remission was similar in all patients, and no serious infections, cancer, or deaths were reported. Conclusions: Anti-TNF therapy and accelerated step-up in older patients with more severe disease leads to beneficial long-term outcomes.